Stance symmetry and sway after stroke - Sackley, Catherine Mary (1991)
The aim of the study was to investigate the assessment and treatment of stance symmetry and sway after stroke and was divided into 3 parts. Stage 1. Sway and stance symmetry were surveyed with the Nottingham Balance Platform (NBP), a computerised limb load monitor. Over 400 volunteers of both sexes and a wide age range were recruited. There were significant differences between the sexes for both sway (p<0.05) and stance symmetry (p<O.Ol) and significant correlations between age and sway (p<O.OOl) and stance symmetry (p<O.OOl). Thus, normative data was provided. Stage 2. Patients were surveyed to examine these variables after stroke and their relationships with age, falls and motor and ADL function. A consecutive sample of 92 patients underwent 2 assessments, 4 months apart, between 2 and 9 months post-stroke. Abnormal stance symmetry was seen, which improved with time (p<O.01) and correlated with functional measures (p<.001), length of stay and age. Abnormal sway values also present, improved with time (p<O.Ol). A significant relationship existed between sway values and falls frequency (p<O.01), but there was no significant association with functional abilities, age or sex. Stage 3. A single-blind randomised-controlled trial was conducted with 26 stroke patients to assess the value of visual feedback training. Patients demonstrating asymmetry were randomly allocated to two groups. Group A received visual feedback and Group B a placebo program, incorporated into 12 physiotherapy sessions. Independent assessments of motor and ADL function were completed at the start (0 weeks) and end of treatment (4 weeks) and at 8 weeks. Initially, there were no significant differences between the groups. At 4 weeks, stance symmetry and measures of function were significantly better for the treatment group than controls (p<0.05), but not at the final assessment. The improvement, although maintained, did not continue after treatment. The results support the further use of feedback techniques to improve standing posture after stroke.